Development of a Risk Preventable Emergency Referral System of a 5-Health-Care Network, Chieng Rai Province, Thailand - Buranabenjasathian, Sudanee (Journal of Health Science of Thailand, 2017)
Mae Chan Hospital is the main of health care service for 5 hospitals in the northern zone of Chiang Rai province. Initially, the hospital served only tertiary care for orthopedic cases and referred other emer gency patients to Chiang Rai hospital in the provincial center. Such practice occasionally resulted in undesirable events relating to the transfer of emergency patients. The objective of this study was to develop a system to prevent adverse events through the formation of a system for the referral of emergency patients. It was conducted during October 2014 to September 2015; and the process was performed in 3 phases: (1) situation assessment and development of a suitable model involving the 4 other hospitals in the network; (2) operation of the model and data collection, and (3) data analysis. It was found that the model was feasible and effective. There was a formation of a committee with clearly specified responsibility; and gradual system improvement was obsrved. The system was able to reduce undesirable management and clinical events from 31.71 and 42.54 to 5.60 and 13.13 per 1,000 referred cases respectively.